Ensuring Information Disclosure and Environmental Impact on Nanoradioactive Operation of Civil Nuclear Facilities in China. (10th October 2022) - Liu, Jiu; Shen, Le; Sultana, Kakon
Abstract : Japan was struck by a massive earthquake that triggered a tsunami in March 2011, which led to a severe nuclear accident at the Fukushima Daiichi Nuclear Power Plant of the Tokyo Electric Power Company. Now, more than 10 years later, it is widely acknowledged that the civil nuclear industry is of great importance in reducing greenhouse gas emissions, improving natural environmental quality, and safeguarding national energy security. Nanomaterials and nanotechnologies, which have gained wide consideration in recent years, have shown a wide variety of application potentials in the future nuclear energy system. Thus, China has been developing its civil nuclear industry throughout the years, despite the nuclear accident in Fukushima, Japan. As a result, China is currently one of the countries with the most nuclear power plants. However, due to the potential radioactive risk, the public has an instinctive fear of civil nuclear development. To alleviate the public's antinuclear sentiment, the Nuclear Safety Law was formally implemented in 2018, and Measures for Disclosure of Nuclear Safety Information were issued by the Ministry of Ecology and Environment of China in 2020, both stipulating that the public has the right to obtain information about nuclear safety and be involved in related activities. The purpose of such legislation is to eliminate the public's doubts and phobia about the development of the civil nuclear industry. However, challenges still exist. Although such suggestions have been proposed, such as information disclosure and social involvement should begin as early as the siting of such nuclear facilities, mechanisms to provide sufficient compensation to the public living near nuclear facilities should be established, and these suggestions still have not been applied in the law of China and either not been practiced exactly so far. So, even though all the suggestions have strong feasibility themselves under today's circumstances in China, it is not easy to judge the effectiveness of these suggestions until they are fully practiced. It is the biggest problem of existing works in this paper. To highlight the serious problems in information disclosure and public involvement in the siting and construction of civil nuclear facilities, several case studies were investigated as the major methodology in this research. Moreover, a legislation study was used to analyze the current content of related legislation and regulations. A qualitative methodology was also adopted to summarize the legal problems surrounding information disclosure and social involvement during the siting and construction of civil nuclear facilities. Information disclosure and public participation still face several obstacles in China, even though laws and regulations guarantee people the right to access available information and take part in pertinent decision-making. This is particularly true when it comes to the siting and construction of civil nuclear facilities. Thus, in the last several years, several antinuclear incidents have been initiated by the public due to a lack of information and mechanisms to participate. According to the examined cases, information disclosure and public involvement are still not sufficient during the siting of nuclear facilities. A relevant compensation mechanism for people living around nuclear facilities has not been established, and public education on basic nuclear safety is lacking. Therefore, public involvement cannot be completely realized. To ensure information disclosure and public involvement in civil nuclear facilities, this article proposes that information disclosure and social involvement begin as early as the siting of such facilities. Furthermore, operators of nuclear facilities and local governments should establish mechanisms to provide sufficient preventive compensation to the public living near nuclear facilities and attempt to popularize the science of nuclear safety to avoid public misunderstanding.